Efficacy and Acceptability of Orthokeratology for Slowing Myopic Progression in Children: A Systematic Review and Meta-Analysis - Daizong Wen; Jinhai Huang; Hao Chen; Fangjun Bao; Giacomo Savini; Antonio Calossi; Haisi Chen; Xuexi Li; Qinmei Wang (Journal of Ophthalmology)
Background. To evaluate the efficacy and acceptability of orthokeratology for slowing myopic progression in children with a well conducted evidence-based analysis. Design. Meta-analysis. Participants. Children from previously reported comparative studies were treated by orthokeratology versus control. Methods. A systematic literature retrieval was conducted in MEDLINE, EMBASE, Cochrane Library, World Health Organization International Clinical Trials Registry Platform, and ClinicalTrials.gov. The included studies were subjected to meta-analysis using Stata version 10.1. Main Outcome Measures. Axial length change (efficacy) and dropout rates (acceptability) during 2-year follow-up. Results. Eight studies involving 769 subjects were included. At 2-year follow-up, a statistically significant difference was observed in axial length change between the orthokeratology and control groups, with a weighted mean difference (WMD) of −0.25 mm (95% CI, −0.30 to −0.21). The pooled myopic control rate declined with time, with 55, 51, 51, and 41% obtained after 6, 12, 18, and 24 months of treatment, respectively. No statistically significant difference was obtained for dropout rates between the orthokeratology and control groups at 2-year follow-up (OR, 0.79; 95% CI, 0.52 to 1.22). Conclusions. Orthokeratology is effective and acceptable for slowing myopic progression in children with careful education and monitoring.